Corporate Governance Mechanisms and Financial Performance: An Analysis of Listed Companies in Brazil - Oliveira, Juliana Costa (International Journal of Strategic Management, 2024)
Purpose: The aim of the study was to investigate the corporate governance mechanisms and financial performance: an analysis of listed companies in Brazil. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The analysis of listed companies in Brazil found that strong corporate governance practices are associated with improved financial performance. Factors such as board independence, transparency, and shareholder rights positively influence profitability, liquidity, and market valuation. This highlights the vital role of effective corporate governance mechanisms in fostering investor confidence and driving sustainable financial success in Brazil. Unique Contribution to Theory, Practice and Policy: Agency theory, stakeholder theory & resource dependency theory may be used to anchor future studies on the corporate governance mechanisms and financial performance: an analysis of listed companies in Brazil. By emphasizing the pivotal role of board independence, transparency, and shareholder engagement, the study provides tangible guidance on governance practices that can be effectively implemented to bolster financial performance. Policymakers tasked with overseeing the corporate governance landscape in Brazil